2018
DOI: 10.7759/cureus.2874
|View full text |Cite
|
Sign up to set email alerts
|

A Variant of the Sciatic Nerve and its Clinical Implications

Abstract: Variants of gluteal neural anatomy are important to consider, especially during surgical approaches to the hip. During the routine dissection of the gluteal region, a variant of the sciatic nerve was found where the nerve left the pelvis fully split into its tibial and common fibular components. Intrapelvically and extrapelvically, there was no splitting of the two components by the piriformis muscle. Distally, the two parts of the nerve were draped over the medial and lateral edges of the ischial tuberosity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…A study by Antoniadis reported [ 6 ] that 25% of symptomatic SN lesions were iatrogenic, whether through surgical trauma or anesthetic mishaps, highlighting the difficulty in identifying and isolating the SN. Just as Dupont et al [ 7 ] suggest, a thorough survey of a patient’s SN course needs to be appreciated prior to treatment in order to minimize the risk of iatrogenic injury, which must be preceeded by an understaning of all the possible SN variations.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Antoniadis reported [ 6 ] that 25% of symptomatic SN lesions were iatrogenic, whether through surgical trauma or anesthetic mishaps, highlighting the difficulty in identifying and isolating the SN. Just as Dupont et al [ 7 ] suggest, a thorough survey of a patient’s SN course needs to be appreciated prior to treatment in order to minimize the risk of iatrogenic injury, which must be preceeded by an understaning of all the possible SN variations.…”
Section: Discussionmentioning
confidence: 99%
“…where the CFN split superior to and the TN passed inferior to the superior gemellus muscle [9]. Furthermore, in rare cases, the sciatic nerve has been found to split before reaching the PM in a manner where the CFN and TN travel on both sides of the ischial tuberosity [10].…”
Section: Discussionmentioning
confidence: 99%
“…It originates from both posterior and anterior divisions of the ventral rami of L4, L5, S1, S2, and S3 nerve roots. The SN leaves the pelvis through the sciatic foramen, below the piriformis muscle (15,16).…”
Section: Anatomymentioning
confidence: 99%